Semiotic Analysis of Racism Using IP Man 4: The Finale - Muhammad` Afra Masyhur; Suprayogi Suprayogi (Universitas Pendidikan Indonesia, 2021)
Racism, prejudice and discrimination are complex things that occur in this world, according to Baldwin (2017) this is a broad social phenomenon and a field for research, complicated by the fact that intolerance exists in internal cognition but manifests in the use of symbols (verbal, nonverbal). , mediation), law and policy, and social and organizational practice. It is based on group identification (ie, understanding and treating a person or persons in terms of outgroup membership); but those outgroups can range from better-known outgroups based on race, gender/gender, nationality, or sexual orientation to more specific intolerance of others based on political party, fan status, or membership in some groups perceived as